Photovoltaics: Photovoltaic Voltage Regulation through Distributed Power Compensation Considering Communication Delay (Adv. Theory Simul. 1/2020). Issue 1 (3rd January 2020) - Zhang, Zhanqiang; Dou, Chunxia; Yue, Dong; Zhang, Bo; Zhang, Tengfei
Abstract : A photovoltaic power compensation scheme is developed to address the overvoltage problem. Based on an estimate of maximum tolerable communication delay, a predictive compensation method is proposed to ensure voltage regulation under abnormal communication delay. More details can be found in article number 1900148 by Chunxia Dou, Dong Yue, and co‐workers.